Arts-based action research on enhancing children’s creativity through affect within participatory performance art and performance pedagogy - Griniuk, Marija (Creativity Studies, 2021)
This article presents arts-based action research on enhancing children’s creativity through affect within participatory performance art and performance pedagogy. The study hypothesis was that children’s creativity can be enhanced by affect experienced at a performance site. The purpose of the study was to investigate the impact of children’s involvement in artistic performance on their creativity at a performance site. The impact of interactions at the site, the co-participating children,and the involved artists were monitored on a daily basis to collect qualitative data, which were analyzed using a general inductive approach. Objective themes relating to the variables were retrieved from the collected data and assigned codes, concepts, and keywords extracted from photographs,video recordings, and observation notes. The case under investigation was the “Nomadic Radical Academy 2020: The Good, the Bad, and the Art”, which built on a pilot event held in 2019. This research concluded that performance art can have a social and creative impact during an art event through children’s participation and can be used by performance artists and educators.